Bladder pain syndrome. Issue 11 (November 2018) - Uddin, Mohsin; Azhar, Fowz; Pearce, Ian
Abstract: BPS is a condition of chronic bladder pain or discomfort that can significantly disrupt normal daily activities and decrease quality of life. It often remains difficult to diagnose and manage because of vague symptoms, the aetiology is not well understood and there is a lack of universally effective treatments. This article reviews the current literature about BPS etiology, clinical presentation, diagnosis, and treatment options. Our search was limited to the articles, on the "diagnosis", and "management" or "treatment" of "interstitial cystitis" and the "bladder pain syndrome".